Efeito da cobertura plástica no desempenho de uma lagoa anaeróbia tratando efluente de indústria de fécula de mandioca - Pontello, Clori Jose (2005)
Manioca starch mills generate a high amount of outflow and environmental concerns due to its high pollutant wastewater. Use of stabilization ponds is very common for the treatment of wastewater on the transformation of manioca root sector. However, in winter time, coincidently with the harvesting and crushing period a fall on the treatment system may occur due to the decreasing of environmental temperature. The present study aims at evaluating the effect of plastic canvass on the stability and keeping the anaerobic pond temperature treating the outflow of cassava. The system consisted of two reactors simultaneously supplied, with net volume of 15.98m3 each, 10 day hydraulic retaining time, continuously supplied, without pH correction and without temperature control. Air temperature and daily outflowing and inflowing of the reactors were monitorized for a period of one year. Both physical and chemical analyses were performed measuring pH, BOD5, COD, TSS, FSS, and VSS of the reactors outflowing and iinflowing in monthly frequency. The daily temperatures measured on the covered reactors were superior than on the uncovered ones. An efficiency of 10% on COD, and 15% on BOD5 were observed on the covered reactor. The plastic canvass covered reactor showed less oscilations with greater stability in keeping temperatures, mainly in periods of low temperature, showing a better performance on the treatment of cassava processing outflow.